2018
DOI: 10.1186/s12885-018-4308-7
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib versus Transarterial chemoembolization for advanced-stage hepatocellular carcinoma: a cost-effectiveness analysis

Abstract: BackgroundSorafenib and transarterial chemoembolization (TACE) might both provide survival benefit for advanced hepatocellular carcinoma (HCC). Adopting either as a first-line therapy carries major cost and resource implications. We aimed to estimate the cost-effectiveness of sorafenib and TACE in advanced HCC.MethodsA Markov model was constructed in a hypothetical cohort of patients aged 60 years with advanced HCC and Child-Pugh A/B cirrhosis over a 2-year time frame. Three strategies (full or dose-adjusted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…For example, Cabibbo et al report that median OS and median time to radiological progression are separately 10.0 and 4.1 months in the patients with SOR treatment, which help guide doctors to replace second-line therapies in a timely manner [ 21 ]. Chen et al compare SOR with transarterial chemoembolization (TACE) and suggest that dose-adjusted SOR may be cost-effective than TACE for advanced HCC patients, which provide a basis for doctors to improve efficacy and reduce medical costs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cabibbo et al report that median OS and median time to radiological progression are separately 10.0 and 4.1 months in the patients with SOR treatment, which help guide doctors to replace second-line therapies in a timely manner [ 21 ]. Chen et al compare SOR with transarterial chemoembolization (TACE) and suggest that dose-adjusted SOR may be cost-effective than TACE for advanced HCC patients, which provide a basis for doctors to improve efficacy and reduce medical costs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al showed that TACE and sorafenib treatment have different costs because of different medical charging systems among countries. In US one TACE session costs are more than 5.5 times of the monthly cost of full‐dose sorafenib whereas the costs of TACE procedure in China are lower than the monthly cost of sorafenib 28 . The overall costs incurred by the Italian National Healthcare System for the treatment of intermediate HCC are similar when one TACE session costs are compared with the monthly cost of full‐dose sorafenib 29 …”
Section: Discussionmentioning
confidence: 99%
“…In US one TACE session costs are more than 5.5 times of the monthly cost of full-dose sorafenib whereas the costs of TACE procedure in China are lower than the monthly cost of sorafenib. 28 The overall costs incurred by the Italian National Healthcare System for the treatment of intermediate HCC are similar when one TACE session costs are compared with the monthly cost of full-dose sorafenib. 29 Based on these considerations, both data on clinical efficacy and cost-effectiveness analysis are required to find the best and conclusive treatment strategy for the treatment of intermediate-stage HCC in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Now, heading to the Markov models, a Canadian model has evaluated the cost‐effectiveness of sofosbuvir/velpatasvir treatment for patients with decompensated cirrhosis, stating that it provided an added four quality‐adjusted life years (QALY), at a cost of $39.169, rendering the approach cost effective at the set threshold of $50.000/QALY 51 . On the other hand, data regarding TACE come as follows: it appears that TACE generates in various settings up to a maximum of three QALYs, never exceeding $50.000/QALY 52–55 . Of note, not all clinical scenarios include TACE for intermediate stage HCC.…”
Section: Intermediate Stage Hepatocellular Carcinoma: How Does Transartherial Chemoembolization MIX With Direct Acting Antivirals?mentioning
confidence: 99%